Acute hemiconcern: a right anterior parietotemporal syndrome. Issue 4 (April 1995) - Bogousslavsky, J; Kumral, E; Regli, F; Assal, G; Ghika, J
Abstract : Three patients developed a striking visual and motor behaviour in the acute phase of a stroke involving the territory of the right anterior parietal artery (postcentral gyrus, parts or upper and middle temporal gyri, anterior part of inferior parietal gyrus, and supramarginal gyrus). The patients concentrated on the left side of their bodies, looking at it for long periods and relentlessly rubbing, touching, pinching, pressing, lifting, and manipulating parts of the left arm, trunk, and leg with their right hand or foot. They all had severe loss of elementary sensation on the left (touch, pain, temperature, vibration, position). The behaviour was not associated with overinterest in the left hemispace apart from their own bodies. It lasted no more than a few days, disappearing when left sided sensation improved. The findings suggest an association between sensory dysfunction and this "acute hemiconcern". None of 13 patients with a mirror infarct in the left hemisphere and none of 38 patients with acute hemisensory loss due to thalamic capsular or brainstem stroke showed hemiconcern behaviour. This behaviour may result from a feeling of strangeness critically associated with hemisensory loss without hemispatial neglect, due to involvement of the right anterior parietotemporal region.